Miltochrista jarawa (Lepidoptera, Erebidae, Arctiinae, Lithosiini), a new species from the Andaman Islands, India - Singh, Navneet; Volynkin, Anton V.; Kirti, Jagbir Singh; Datta, Harvinder Singh (Zootaxa, 2020)
Miltochrista Hübner, [1819] is one of the most species-rich genera of lichen-moths belonging to the Asura/Miltochrista complex and is distributed widely in the Oriental and Palaearctic Regions. A checklist of Miltochrista (sensu lato) was recently published by Volynkin et al. (2019) and included 206 species and 10 subspecies. Four additional species have since been described by Volynkin et al. (2020). But still, the taxonomy of this large and diverse genus is poorly studied and many new species are awaiting descriptions.